"Everybody's Donghu": Artistic Resistance and the Reclaiming of Public Space in China. Issue 4 (November 2022) - Xiao, Jian; Qu, Shuwen
This paper presents a study of an artistic resistance project in China, "Everybody's Donghu (East Lake), " held in 2010, 2012, and 2014 with the aim of intervening in the commercial development of an urban scenic space. It aims to demonstrate the practices of resistance in public spaces, particularly in the context of an authoritarian regime such as China, as opposed to democratic societies. First, the recent development of protest and forms of resistance in China will be discussed. It will then focus on the arising conflicts between the conceptualization of an urban space by the urban planners and the imagination of it by the participants. This is followed by a discussion of the tactics deployed in this event, focusing on how the participants appropriate urban space for their own use through performance. Finally, it explores how technology is used in the practices of resistance, concerning the representation of the area through utilization of online space. Overall, this paper argues that appropriating and representing urban space can open up new possibilities of resistance to power and control in the process of urban transformation.